PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII SMP NEGERI 3 SATU ATAP LAHUSA - Evitina Laia (Curve Elasticity: Jurnal Pendidikan Ekonomi, 2025)
This research aims to determine the application of the Role Playing learning model in improving the learning outcomes of Class VIII Students at SMP Negeri 3 One Roof Lahusa for the 2022/2023 Academic Year. Basically, the purpose of the learning process is to explore students' potentials, interests and talents while participating in teaching and learning process activities which are accompanied by the application of learning models and methods, one of which is the role playing learning model. The research design that will be used in this research is a classroom action research design (PTK). The research instruments used in this research were student observation sheets and subject teacher observation sheets. Based on the research results, it was found that: (1) The Role Playing learning model can improve student learning outcomes in social studies learning with the material Changes in Space and Interaction Between Spaces Due to Natural Factors, this is because by implementing the Role Playing learning model students are more active in learning activities and can understand the concept of the material well. (2) Student learning outcomes increased in the first cycle, it turned out that the percentage of student learning completeness had not met the target set at 70.04%. So it was continued in the second cycle with 81.27%, in the good category because the results showed good results. Based on the level of student learning success, in this case the success target has been achieved to meet the minimum completeness criteria. Based on the presentation of the research data, it can be concluded that there has been an increase in student learning outcomes through the role playing learning model in improving the learning outcomes of class VIII students at SMP Negeri 3 One Roof Lahusa for the 2022/2023 academic year.